PENERAPAN MODEL PEMBELAJARAN GENERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA MATERI KONDISI GEOGRAFIS DAN PENDUDUK PADA KELAS VII2 SMP NEGERI 2 KONAWE - Feri Setiawan, Iskandar (Jurnal Penelitian Pendidikan Geografi, 2018)
the problems examined are: 1 learning activities of students. 2)  Teacher teaching Activity.  3) Improving learning results. The aims  of this research to.  1) Improve the students learning activity  , 2) increases teacher teaching activity.  3) Knowing the increase in the results of the study. This  study is An action classroom Research, which has been implemented in  2 cycle. The subject of this research  the students are registered on the even- in academic year of  2016/2017, numbered 20 students. The date of this research is the activity of teacing process of teacher and learning activities of the students which obtained from the observation sheet and the results of learning as measured through tests. Date analysis was conducted a descriptive statistic. The results showed if. 1) learning activities at each cycle tends to increase. This is demonstrated by average score on each cycle, in cycle I score average is 2.7 students activity increased in cycle II becomes 3.25. 2) on cycle I score an average teacher's teaching activity is increased 2.85 cycle II becomes 3.65. 3) results of study geography enhanced through generative learning model. On cycle I students who finished 13 (65%) and not completely and absolutely no 7 (35%)  with an average of 72.25 whereas  at the second cycle was increased to 17(85%) The students who did not complete 3 students (15%).